3D ISPH erosion model for flow passing a vertical cylinder. (April 2018) - Wang, Dong; Shao, Songdong; Li, Shaowu; Shi, Yang; Arikawa, Taro; Zhang, Hongqian
Abstract: In this paper a 3D incompressible Smoothed Particle Hydrodynamics (ISPH) erosion model is proposed to simulate the scouring process around a large vertical cylinder. The erosion model is based on the turbidity water particle concept and the sediment motion is initiated when the fluid bottom shear stress exceeds the critical value. The previous 2D SPH sediment initiation model is expanded by combining the effects of both transverse and longitudinal sloping beds in a practical 3D situation. To validate the developed model, a laboratory flume experiment was carried out to study the clear water scouring around a vertical cylinder under unidirectional current, in which high-speed video cameras were used for the real-time monitoring of sediment movement. The 3D ISPH results are compared with the experimental data with good agreement in terms of the scouring patterns and scales. Besides, the computed flow velocity field suggests that both the horseshoe vortices and lee-wake flows around the cylinder have been realistically simulated.